Magnetic anisotropy and relaxation behavior of six-coordinate tris(pivalato)-Co(ii) and -Ni(ii) complexes. Issue 30 (16th July 2018) - Chen, Shu-Yang; Cui, Hui-Hui; Zhang, Yi-Quan; Wang, Zhenxing; Ouyang, Zhong-Wen; Chen, Lei; Chen, Xue-Tai; Yan, Hong; Xue, Zi-Ling
Abstract : Magnetic measurements, HFEPR and theoretical calculations have been used to study the magnetic anisotropy of the six-coordinate field-induced single ion magnet (NBu4 )[Co(piv)3 ] and its Ni analogue. Abstract : Experimental and theoretical studies of magnetic anisotropy and relaxation behavior of six-coordinate tris(pivalato)-Co(ii ) and -Ni(ii ) complexes (NBu4 )[M(piv)3 ] (piv = pivalate, M = Co, 1 ; M = Ni, 2 ), with a coordination configuration at the intermediate between an octahedron and a trigonal prism, are reported. Direct current magnetic data and high-frequency and -field EPR spectra (HFEPR) of1 have been modeled by a general Hamiltonian considering the first-order orbital angular momentum, while the spin Hamiltonian was used to interpret the data of2 . Both1 and2 show easy-axis magnetic anisotropies, which are further supported by ab initio calculations. Alternating current (ac) magnetic susceptibilities reveal slow magnetic relaxation at an applied dc field of 0.1 T in1, which is characteristic of a field-induced single-ion magnet (SIM), but2 does not exhibit single-ion magnetic properties at 1.8 K. Detailed analyses of relaxation times show a dominant contribution of a Raman process for spin relaxation in1 .